PROTETORES SOLARES À BASE DE FILTROS INORGÂNICOS: DESENVOLVIMENTO E CARACTERIZAÇÃO - Tolotti, Michele Fabricia (2012)
The inorganic sunscreens represented mainly by titanium dioxide (TiO2) and Zinc Oxide (ZnO), were classified as inert particles, therefore, they are pointed out as the best way to protect the skin against the harmful effects of ultraviolet radiation (UV). However, recent studies suggest that these particles have several stability problems that may lead to a compromise of safety and efficacy of photoprotective products. In this sense, the hydroxyapatite (HAP) has been investigated as an alternative to sunscreen formulation, playing the role of inorganic filter. Viewing the need for the development of sunscreens with low biological risk and high sun protection factor (SPF) based on inorganic filters, the present work aimed to investigate optimization mechanisms of the sunscreen based inorganic filters formulation. Thus, were evaluated the influence of coating and particle size on the photocatalytic activity of ZnO, TiO2 and HAP in the presence to UVA, UVB and UVA/UVB radiation by analysis of the rate of degradation of the organic substrate methylene blue. Employing optical microscopy, were investigated possible incompatibilities between the inorganic filters and different alpha hydroxyacids commonly used in products containing SPF. Were developed sunscreens based on micronized ZnO, TiO2 alumina, ZnO + micronized TiO2 alumina and HAP containing 15% of inorganic filter. Were prepared oil-in-water (O/W) creams from the variation of the concentration and nature of emollient agents, nonionic co-emulsifier and film-former. The influence of preparation method on the physicochemical properties of sunscreens was evaluated using two different methods: incorporation of inorganic filters to the vehicle by means of a pre-dispersion and the conventional method. In order to evaluate the behavior of components that can interfere with the SPF and stability aspects of the formulation, were developed pre-dispersions added of Shea Butter. All formulations developed were physicochemically characterized and subjected to stability tests. The zeta potential and average particle size was measured using a Zetasizer 3000 HSA. Using a photoacoustic spectrophotometer, were analyzed the ability of UV light absorption of the sunscreens developed. The photocatalytic study suggested that the coating inorganic filters represents the best alternative to inhibit the photocatalytic activity of these particles. Glycolic and lactic acids showed incompatibilities only with ZnO. In photoacoustic analysis, it was found that the products have an effective UV absorption, as inorganic filter characteristics The physicochemical characterization and stability analysis propose that the formulation method from a pre-dispersion is most suitable for obtaining a stable and secure sunscreen product. The HAP-based formulations, however, represented an exception, because they were stable regardless of the method of incorporation into the cream base. In summary, the results indicate that, to obtain a safe and effective sunscreen, is extremely important we focus on the formulation criteria, such as ideal choice of components and technical preparation.